Prevalence of Various Sign and Symptoms of Diabetic Peripheral Neuropathy - Asif, Kahkshan; Qurat ul ain (BioSight, 2021)
BACKGROUND: Diabetes mellitus (DM) is a chronic metabolic syndrome marked by hyperglycemia due to absolute or relative deficiency of insulin hormone. Diabetic neuropathy is a complication of both type 1 and type 2 diabetes. Although pain is one of the most dominant symptoms of diabetic neuropathy, its pathophysiological mechanisms yet unknown. Toxic effects of high glucose levels play an important role in the development of this complication. METHODOLOGY: Data was collected through the questionnaire regarding Clinical findings, medical records, weight, age, family history, different habits, and psychogenic behavior. All the patients with the mentioned diseases are included in this study, excluding the mentally ill patients and the pregnant women. RESULT: The result of the present study showed that diabetic neuropathy is the most common complication of diabetes mellitus. It has been observed that most of the patients due to lack of awareness are suspected to the elevated or extreme blood sugar level which leads to neuropathy. Due to the Diabetic Peripheral Neuropathy (DPN) most of the patients suffering from foot problems, foot ulcers and then amputations. Lack of awareness, lack of health management, obesity, blood pressure changes, less care plays a key role in increasing the chances of diabetic neuropathy. COCLUSION: Diabetic neuropathy had very bad influence on a person’s health and daily activities. The Patient education programs need to emphasize on large scale. The ultimate aim of this study is the foot care education for people with the diabetes and to prevent foot ulcers and amputation.